ENVIRONMENTAL SOSTENIBILIDAD AND SOCIAL RESPONSIBILITY IN THE AURIFEROUS ACTIVITY: THE CASE OF PIERINA (ANCASH) - Dionicio Padilla, Eusebio (2008)
The research present had have two aspects: The environment sustain and social responsability. The environment sustain was studied the quality waters and the sediments in the three creaks mine Pierina: Creaks Pacchac, Pucauran and Llancash; thus the points: up river Mullaca of Santa river, point Lima, Jangas bridge and Paltay river, the result are part the research present. The particles material for sediments was done in the towns: Soledad, Shancayan, Llactash, Shimpi, Jangas and Carhuaz, going Huaylas route, obtained dust during 60 days, and this was analyzed As and Pb. Due to environment impact the Pierina mine will have a clousing mine and ricovering environment pasive and afflorestation wich are been excecuted and the future clousing of layers of lixiviation. This process last 9 years.At 2005 december the company has supply Us$ 99,7 millons for clousing mine.